Optical properties comparison of carbon nanodots synthesized from commercial granulated sugar using hydrothermal method and microwave. (21st August 2019) - Dwandaru, Wipsar Sunu Brams; Bilqis, Silma Maulana; Wisnuwijaya, Rhyko Irawan; Isnaeni,
Abstract: Optical properties comparisons of carbon nanodots (C-dots) from commercial granulated sugar via hydrothermal method and microwave have been conducted. The granulated sugar mass is varied, i.e.: (in grams) 10, 20, and 40, each dissolved into 250 ml of distilled water. The hydrothermal method is performed by heating the sugar solution in an autoclave inside an oven for 5 h at 150 °C, while the microwave technique is done by heating the sugar solution inside a microwave oven for 40 min. The resulting colours of the C-dots solutions using the hydrothermal method and microwave are light to dark brown and yellow to dark brown, respectively. The C-dots are characterized using UV–vis, PL, TRPL, and FTIR spectroscopies, and also TEM. The general optical properties of the C-dots obtained from both synthesis are similar, but different in the details. These general optical features of the C-dots are brownish colored solutions, green luminescence, and spherical shaped particles. The differences of the C-dots from the microwave technique compared to the hydrothermal method include: a shorter UV–vis wavelength at maximum absorbance values of the core, broader PL wavelength at the emission peaks, faster emission time of TRPL, and smaller diameter size of the particles.